In silico binding interactions of dehalogenase (Dehe) with various haloalkanoic acids - Abdul Halin, Nur Illani; Huyop, Fahrul Zaman; Tengku Abdul Hamid, Tengku Haziyamin; Abd Halim, Khairul Bariyyah; Abdul Hamid, Azzmer Azzar (Razi Publishing, 2017)
Synthetic haloalkanoic acid (HA) is one of the synthetics compounds that can be found as active ingredients in herbicides. These compounds are known to pollute our agriculture land due to their toxicity, thus may cause serious environmental and health problems. Biological process such as microbial dehalogenation degrades the harmful compounds and prevents their migration into groundwater source. For instance, Rhizobial Dehalogenase E (DehE) could catalyze these HA compounds and convert them into hydroxylated compounds which are less harmful to the environment. In previous study, DehE was considered to degrade many HA compounds with different Km values. However, the binding interaction of this enzyme towards many HA substrates is still unclear. In this study, docking simulation has been performed to determine the affinity of active site residues of DehE towards 15 HA compounds. Tribromoacetic acid (TBA) was identified to be the most favourable substrate for DehE which has the lowest binding energy (-6.48 Kcal/mol) compared to other haloalkanoic acids. Size of halogen and hydrogen bond numbers are the contributing factor for dehalogenase affinity towards its substrates. Besides, it was found that Trp34, Phe37 and Ser188 served as binding residues and Phe37 was mostly interacted and bound with all of the tested HA compounds. This findings provides an opportunity for rational design of haloacid dehalogenase especially to DehE.